Assessment of the performance of the graduates of the selected aspects of competency-based BSN curriculum - Cuevas, Teresita L. (1990)
The Bachelor of Science in Nursing (BSN) curriculum has come up with terminal competencies designed to prepare nurses who can function in 1st level position in hospital and community settings. It resent updating to suit the country's demands for quality health care provides a timely opportunity to determine whether its 1st products, the 1988 and 1989 graduates, perform satisfactory in the 5 areas of nursing performance as provided by themselves and as observed directly by the investigator. This study focuses its main analysis on DECS competency-based curriculum with a particular look on the 3rd and 4th levels including the specific objectives, activities and expectations on these particular competency strata. The theoretical framework of this study was based on the view that new graduates have the nursing responsibilities and terminal competencies expected to function as a 1st level practitioner upon completion of the BSN program. The concept developed in this study was that academic preparation is related to the quality of the work performance of the graduates. In this study, schools where these nurses graduated from were compared to determine their competency levels of performance in terms of 5 aspects of nursing care. The schools are grouped into 3 categories: School 1, the University of the Philippines College of Nursing, School 2, the Metro Manila nursing schools; and School 3, the Provincial Nursing schools. The nurses' performances are affected by the school where they graduated. The dependent variables are the observed performance and the perceived performance of the nursing graduates in terms of 5 aspects of nursing care. This study was conducted in 4 selected major wards of the Philippine General Hospital from May 14 to July 13, 1990. Forty-six nurses were chosen randomly from the surgical, medical, obstetric and pediatric wards. The findings of the study signal health educators, nursing service leaders, nurse practitioners, and citizens to collaborate in determining future health care needs and nurse practice patterns so that the corresponding changes needed in education can be made. Furthermore, changes have to be affected in health care agencies which will be recipients of these future graduates to enable nursing graduates to practice as predicted in an environment which is receptive to them and which fosters their continuing professional growth.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Nursing curriculum; Nurses -- Competencies